PELAKSANAAN PROGRAM TAX AMNESTY DALAM RANGKA MENINGKATKAN KEPATUHAN WAJIB PAJAK BADAN - Murweni, Ira; ., Gunardi (ANALISIS FAKTOR-FAKTOR PENYEBAB TERJADINYA KREDIT MACET PADA KUD RAHMAT WIDODO KECAMATAN SRUWENG KABUPATEN KEBUMEN, 2018)
Tax Amnesty is one type of government policy that is used to accelerate economic growth and restructuring through the transfer of assets, which will affect domestic liquidity improvements, improve rupiah exchange rate, decrease interest rates, and increase investment, and increase tax revenues, others will be used for development financing. This study aims to measure the extent to which the success of the tax amnesty program implemented by the Government of the Republic of Indonesia during the period 2016 - 2017 in order to improve compliance with corporate taxpayers. The research method used in this research is quantitative descriptive by using secondary data that is the amount of tax amnesty fund receipt during Period I: from the date of enactment until September 30, 2016; Period II: From October 1, 2016 to December 31, 2016, and Period III: from 1 January 2017 to 31 March 2017 and the amount of corporate and personal taxpayers attending the program. Tests conducted on the amount of tax agencies that make the redemption of property and the number of applicant?s tax amnesty program with the amount of tax amnesty and tax revenue in the same period. While the analysis of research data used is multiple linear regression analysis at a significant level ? = 0.05 with the number of samples as many as 32 secondary data processed with SPSS software version 21 for Windows. Results The results of the t-independent test show that the implementation of the tax amnesty program is generally effective in improving taxpayer compliance.